`Top-level women`s football coaches: Tracing exceptional career pathways`, a research project funded by the João Havelange Research Scholarship - Barker-Ruchti, N.; Hofmann, A.; Lindgren, E. C.; Shelton, C.; Sinning, S. (International Centre for Sports Studies (CIES), 2013)
Background: Most coaches are men. In football, several high-profile coaches are women. Most research on women`s coaching career pathways has focused on their difficulties in developing careers. The complexity of professional learning and personal development has received particularly little attention, and has to date only been examined within sport. How learning outside of sport relates to career development has not been studied. Purpose and objectives: The purpose of this study is to produce socio-cultural knowledge about successful top-level women football coaches. The specific objectives of this research are to: (1) Trace the career pathways of top-level women football coaches; (2) Describe their professional learning and development and examine how these relate to career progression; and (3) Develop recommendations for stakeholders to recruit and develop more women football coaches. Research methodology: The study is designed as a multiple-case study. Semi-structured interviews were conducted with 19 national and top-league team coaches. A survey asking for demographic information and a biographical mapping technique was employed to support the interviews. All interviews were transcribed and where necessary, translated into English. The analytic procedure for the final report was conducted by the entire research team and involved a content analysis. The theoretical perspectives that are developed to interpret the findings are derived from a social constructivist perspective of learning, including `cultural theory of learning` and `careership`. Further, the project`s data will be analysed for scientific publications. The different analytic foci are: a) International football as a learning culture; b) Knowledge acquisition and coaching practice; c) Turning points and career development; and d) Development of women`s football. Findings: The two key findings for objective 1 are that the women coaches did not strategically envisage and pursue a full-time coaching career and that institutional support reinforced coaching career development, while a lack of such support created dual professional careers. Both pathways have advantages and disadvantages. The key finding for objective 2 is that learning from all spheres the women coaches occupied related to the development of a coaching career. The learning that took place was tied to a vision to become/develop careers. Differences in organisational support affected how coaching career visions became established. Coaches with institutional support developed the vision as they were offered full-time football work; coaches with no institutional support developed the vision over a longer period of time and through various serendipitous and opportune events and learning. Recommendations: Key recommendations for women players/coaches are to become involved, to actively create coaching career visions and to network; for football clubs, recommendations include to actively engage and support women coaches, and to support and appreciate women`s learning outside of sport; and for football organisations, key recommendations are to actively recruit and support football organisations` efforts to engage women coaches, to provide purposeful learning opportunities, and to use top-level coaches as role models and ambassadors. Introduction Most sport coaches are men. Research consistently reveals that only very few women enter coaching and progress in their coaching careers (Acosta & Carpenter, 2000; Carpenter & Acosta, 2008; Sinning, 2005). Women`s football can be considered an exception. More women currently hold national football team coaching positions than in any other team sports (Hofmann & Sinning, 2013). The current and former national head coaches Hope Powell (England), Silvia Neid (Germany), Pia Sundhage (Sweden, US), Martina Voss-Tecklenburg (Switzerland) and Hesterine de Reus (Australia) stand out as some prominent examples. Existing research on women coaches has mostly adopted a deficit and psychologistic approach. Scholars have focused on the representation of women coaches and the disadvantages and barriers they may experience when entering and progressing in their coaching careers (e.g., Fielding-Lloyd & Meân, 2011; Lyle, 2002; Marshall, 2001; Norman, 2010b; Schlesinger & Weigelt-Schlesinger, 2012; Shaw & Allen, 2009; Welch & Sigelman, 2007). How top-level women coaches actually enter and develop successful coaching careers has escaped scientific attention (an exception is the research by Sinning, 2005, 2012). Further, sport coaching career research has to date only produced knowledge about learning career development in sport. Learning outside of sport, as for instance through education and employment in other fields, as well as life in general, have not been related to coaches` pathways. Some career research, however, points to how life experiences affect professional career pathways (Bloomer & Hodkinson, 2000; Hodkinson, Sparkes, & Hodkinson, 1996; Hodkinson & Sparkes, 1997). Turning points, meaning changes to context self, have been found particularly influential (Bloomer & Hodkinson, 2000). Research purpose and objectives The broad purpose of this study is to produce socio-cultural knowledge about successful top-level women football coaches. The specific objectives of this research are to: 1. Trace the career pathways of top-level women football coaches; 2. Describe their professional learning and development and examine how these relate to career progression; 3. Develop recommendations for stakeholders to recruit and develop more women football coaches. In fulfilling the first research objective, the results of this study provide demographic information on the career pathways of women football coaches. This information includes issues such as athletic and educational background, and coach education, experience and positions held. This insight serves to present the coaches as: a) individual role models; and b) collective testimonies that women can develop successful coaching careers. In achieving the second research objective, the results of this study afford insight into when, how and from/with whom the participants of this study learn about coaching methods and practices and develop themselves as individuals and coaches. This information offers insight into the particularities of the communities the women coaches operate(d) in. This includes data on relevant actors within the communities, interpersonal relationships kept within these, values, beliefs, practices, unspoken rules and the work ethic expected and practiced. The data relating to this objective will also focus on life learning. In understanding these specificities, the influence dominant knowledge and discourses, as well as turning points, have on learning and development can be extracted. Here, information on ways the coaches` career development may have been obstructed and what the coaches may have had to do to overcome these, emerges. In relating this information to professional pathways, the coaches` learning can be linked to their career progression. From this, concrete recommendations that develop careers can be formulated. In realising the third research objective, stakeholders within (women`s) football can reflect upon their existing coach recruitment and development strategies. The recommendations will have the potential to guide future recruitment and development systems and practices. Overview of final report Section 1 of the final report outlines existing literature on the topics of women as coaches, coach learning and administration of women`s football. Section 2, which introduces the theoretical perspective that was employed to interpret the data produced in this project. The research methods are then outlined in section 3. The presentation of results in section 4 begins with an introduction of each women coach along the topics of `career as a football player`, `entrance into coaching`, experience and coach education`, `football coaching career`, `education and professional employment outside of football`, `future intentions/perspectives` and `personal challenges` and a copy and interpretations of the completed biographical grids. Similarities and differences among the cases are then summarised. Using the theoretical perspective outlined earlier, these are then interpreted and discussed in section 5. This section is structured along the project`s three research objectives. The last of these three sections includes the recommendations that were developed from this research`s findings and analyses. Section seven concludes the report. An appendix containing the demographic questionnaire and the interview schedule, as well as the literature, complete the report.